(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
With the global growth of tourists only expected to increase, there are endless opportunities for the growth of the tourism industry. Technology has played a major role in the tourism industry which has led to the increase of e-tourism or e-tourism. Tourism has been closely associated with the advancement of information and communication technology for more than 25 years. Nowadays, the Internet and ICTs are relevant at all operational, structural, strategic and marketing levels to facilitate global interaction between suppliers, intermediaries and consumers around the world. In the field of information and communication technologies, we can notice a special focus with regard to the development of a wide range of tools and services that facilitate interaction between market players. at the global level. The development of search engines, transportation capabilities, and speed of networking has affected the number of tourists from around the world who use technology to plan and document their trips